I'm trying to obtain an analytical solution to the following ODE:

$$-\epsilon x y+\left(\epsilon R-x-\epsilon x^2\right)y'+\left(R-x^2\right)y''=0$$

The only method that would make sense for me is the series method where I define $$y=\sum_{n=0}^\infty a_n x^n$$

and try to obtain a recurrence relation.

If each part of the ODE is written separately we obtain:

$$-\epsilon xy = \epsilon \sum_{n=0}^{\infty}a_nx^{n+1}$$ $$\left(\epsilon R-x-\epsilon x^2\right)y'=\sum_{n=1}^{\infty}n a_n x^{n-1}-\sum_{n=1}^{\infty}na_nx^n-\epsilon \sum_{n=1}^{\infty}na_nx^{n+1}$$ $$\left(R-x^2\right)y''=R\sum_{n=2}^{\infty}n(n-1)a_nx^{n-2}-\sum_{n=2}^{\infty}n(n-1)a_nx^n$$

Each time I'm trying to work out the equation I reach a dead end in terms of the indexes. Is it possible to reduce this problem to a recurrence relation problem?

If not, is this equation solvable analytically?


Series representation of each term: $$-\epsilon xy = -\epsilon \sum_{n=0}^{\infty}a_nx^{n+1}$$ $$\left(\epsilon R-x-\epsilon x^2\right)y'=\epsilon R\sum_{n=1}^{\infty}n a_n x^{n-1}-\sum_{n=1}^{\infty}na_nx^n-\epsilon \sum_{n=1}^{\infty}na_nx^{n+1}$$ $$\left(R-x^2\right)y''=R\sum_{n=2}^{\infty}n(n-1)a_nx^{n-2}-\sum_{n=2}^{\infty}n(n-1)a_nx^n$$

You can write these equations as follows $$-\epsilon xy = -\epsilon \sum_{n=0}^{\infty}a_nx^{n+1}$$ $$\left(\epsilon R-x-\epsilon x^2\right)y'=\epsilon R\sum_{n=0}^{\infty}(n+1)a_{n+1} x^{n}-\sum_{n=0}^{\infty}na_nx^n-\epsilon \sum_{n=0}^{\infty}na_nx^{n+1}$$ You can start 2nd and 3rd term of the above series expresions from $n=0$, since for $n=0$ these expressions equal $0$. So, it does not affect the series. $$\left(R-x^2\right)y''=R\sum_{n=0}^{\infty}(n+2)(n+1)a_{n+2}x^{n}-\sum_{n=0}^{\infty}n(n-1)a_nx^n$$ Again, you can start 2nd term of the above series from $n=0$, since for $n=0$ and $n=1$ the term gives you $0$.

Now, the sum of all series expression can be written as $$-\epsilon \sum_{n=0}^{\infty}(n+1)a_nx^{n+1}+\sum_{n=0}^{\infty}\bigg[\epsilon R(n+1)a_{n+1} -na_n+R(n+2)(n+1)a_{n+2}-n(n-1)a_n\bigg]x^n=0$$

Let's modify the 1st term of the above series. $$-\epsilon \sum_{n=0}^{\infty}(n+1)a_nx^{n+1}=-\epsilon \sum_{n=1}^{\infty}na_{n-1}x^{n}=-\epsilon \sum_{n=0}^{\infty}na_{n-1}x^{n}$$ since for $n=0$ it is $0$.

Finally all series expressions can be rewritten as $$\sum_{n=0}^{\infty}\bigg[-\epsilon na_{n-1}+\epsilon R(n+1)a_{n+1} -na_n+R(n+2)(n+1)a_{n+2}-n(n-1)a_n\bigg]x^n=0$$

From the above series, you can determine coeefficient of the series.

  • $\begingroup$ Can you please explain this line $$-\epsilon \sum_{n=1}^{\infty}na_{n-1}x^{n}=-\epsilon \sum_{n=0}^{\infty}na_{n-1}x^{n}$$ $\endgroup$ – jarhead Dec 16 '18 at 10:26
  • $\begingroup$ Left side is $-\epsilon[(1)a_0x+(2)a_1x^2+\dots]$. Right side is $-\epsilon[(0)a_{-1}+(1)a_0x+(2)a_1x^2+\dots]$=$-\epsilon[(1)a_0x+(2)a_1x^2+\dots]$. Two series are the same. $\endgroup$ – Squanch Dec 17 '18 at 22:24

Rewrite the equation as

$$ (R-x^2)(y'' + \epsilon y') - x (y' + \epsilon y) = 0 $$

Let $u = y' + \epsilon y$, then

$$ (R-x^2)u' - xu = 0 $$

Separate and solve to obtain

$$ u = \frac{A}{\sqrt{R-x^2}} $$

What's left is

$$ y' + \epsilon y = \frac{A}{\sqrt{R-x^2}} $$

Use the integrating factor to finish off.

$$ y = Ae^{-\epsilon x} \int_0^x \frac{Ae^{\epsilon t}}{\sqrt{R-t^2}}dt + Be^{-\epsilon x} $$

Note that the solution interval is restricted to $(-\sqrt{R},\sqrt{R})$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.